Cerebrovascular disorders associated with agenesis of the internal carotid artery: Findings on digital subtraction angiography - Xu, Xiaolong; Shen, Hongjian; Ma, Hongyu; Zhang, Xiaoxi; Zhang, Lei; Li, Qiang; Zhao, Rui; Dai, Dongwei; Li, Zifu; Yang, Pengfei; Liu, Jianmin (Frontiers in Surgery, 2022)
Abstract Objective: Agenesis of the internal carotid artery (ICA) is a rare vascular condition that is complicated by intracranial aneurysms and rete mirabile. The altered hemodynamics caused by this distinctive cerebrovascular angioarchitecture can cause ischemic or hemorrhagic accidents. Data on clinical and radiographic features have been limited to describing this vascular pattern. We present five cases of agenesis of the internal carotid artery confirmed by digital subtraction angiography (DSA) and further investigate the influence of altered angioarchitecture on the integrity of intracranial morphology. Methods: Cases of ICA anomalies were screened from the patients who underwent DSA in two hospitals. Clinical manifestation, radiographic features, management, and outcomes were retrospectively reviewed. Results: Five patients (mean age 44 years [range, 30–65 years]) were included. Two patients presented with subarachnoid hemorrhage, one with cognitive impairment, one with dizziness, and one with intermittent headache. DSA demonstrated that three cases were complicated by intracranial aneurysms, one by dural arteriovenous fistula, and one by rete aneurysm. Three patients underwent endovascular treatment and one underwent bypass surgery. No patient died or experienced cerebrovascular accident during short-term follow-up. Conclusions: ICA agenesis can be complicated by disorders such as intracranial aneurysm, rete aneurysm, and dural arteriovenous fistula. This suggests that ICA agenesis is associated with a tendency towards disrupted cerebrovascular homeostasis resulting from altered hemodynamics.